Effect of Ageing on the Mechanical Performance of Thermoset Polymers: A Statistical Approach - Santos, Francisco M. Dos; Oliveira, Lívia Ávila de; Bueno, Alysson H.S.; Silva, Leandro José da; Pino, Gilberto García del; Panzera, Tulio H. (Journal of Research Updates in Polymer Science, 2020)
The present work investigates the effect of three different ageing processes (natural, 100% relative humidity and salt spray) on the mechanical performance of two thermoset polymers, epoxy and polyester, commonly used as matrix phase in composite materials. A full factorial design is conducted to evaluate the effect of significant factors and interactions on moisture absorption, tensile and compressive strength and modulus of elasticity of the thermosets. Both polymers reveal a decrease in moisture absorption in the saline environment compared to the completely saturated condition (100% RH). Polyester polymers in harsh environments exhibit higher compressive properties compared to those subjected to natural conditioning. In general, polyester polymers, which are most affected by the positive effect of additional cross-linking, have less moisture absorption and superior mechanical properties compared to epoxy, which is more affected by the negative effect of plasticization.